2016
DOI: 10.20882/adicciones.728
|View full text |Cite
|
Sign up to set email alerts
|

Comorbilidad psiquiátrica y valores plasmáticos de 2-acilgliceroles en consumidores de alcohol en tratamiento ambulatorio. Análisis de las diferencias de género

Abstract: Alcohol addiction is associated with high psychiatric comorbidity. Objective stratification of patients is necessary to optimize care and improve prognosis. The present study is designed to gain insights into this challenge by addressing the following objectives: a) to estimate the prevalence of psychiatric comorbidities in a sample of outpatients seeking treatment for alcohol use disorder, b) to describe the existence of gender differences and c) to validate 2-acyl-glycerols as biomarkers of alcohol use disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…This one-dimensional score is in agreement with DSM-5 criteria [for more details, see Ref. ( 9 , 19 , 20 , 37 )]. For mental comorbidity associated with substance use disorders, we evaluated mood, anxiety, psychotic, eating, personality (borderline and antisocial personality disorders), and early-onset disorders in childhood [conduct disorder and attention deficit hyperactivity disorder (ADHD)].…”
Section: Methodssupporting
confidence: 79%
See 2 more Smart Citations
“…This one-dimensional score is in agreement with DSM-5 criteria [for more details, see Ref. ( 9 , 19 , 20 , 37 )]. For mental comorbidity associated with substance use disorders, we evaluated mood, anxiety, psychotic, eating, personality (borderline and antisocial personality disorders), and early-onset disorders in childhood [conduct disorder and attention deficit hyperactivity disorder (ADHD)].…”
Section: Methodssupporting
confidence: 79%
“…Notably, patients seeking treatment for cocaine and alcohol use disorders are frequently affected by lifetime psychiatric comorbidity, mainly mood disorders, anxiety, psychosis, and personality disorders ( 9 , 18 20 ). In fact, the diagnosis of various substance use disorders in the same subject (e.g., cocaine and alcohol) is associated with elevated addiction severity, high prevalence of comorbid mental disorders, and difficulty in maintaining abstinence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 162 patients with alcohol addiction, the prevalence of comorbid psychiatric disorders was higher in women (82.5%) than in men (63.9%), with comorbid MD being significantly elevated among the former (67.5% vs. 38.5%). 14 In addition, it was observed that although women start drinking later than men, they take less time to develop dependence symptoms and meet fewer severity criteria than men. In a sample of 55 abstinent cocaine-addicted participants with lifetime cocaine use disorders (15 women and 40 men), women had an increased prevalence of comorbid psychiatric disorders, with 53.3% of them reporting mood disorders in comparison with 32.5% in men.…”
Section: Dual Depression: An Overviewmentioning
confidence: 99%
“…Currently, AUD is a single disorder that integrates both alcohol abuse and alcohol dependence and is characterized by compulsive alcohol use, loss of control over alcohol intake, and a negative emotional state emerging in conjunction with withdrawal and protracted abstinence [ 3 4 ]. AUD is commonly associated with cognitive and memory impairment during development with a higher incidence of comorbid mental disorders, particularly depression and anxiety [ 5 ], and other organic comorbid diseases (e.g., alcohol liver diseases) [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%